Current Status and Future Prospects of Rajasthan Fisheries - Rohitash Yadava; N. K. Chadha; V. P. Saini; Rajpal Yadava; P. B. Sawanta; M. L. Ojha; Manish Jayant; B.K. Sharma (Journal of Indian Fisheries Association, 2020)
The State of Rajasthan has vast water resources in reservoirs, lakes (freshwater and salt lakes), ponds, rivers, canals, and waterlogged bodies. The total inland water resources include reservoirs, ponds, tanks (4.23 lakh ha), rivers and canals (30,000 ha), wetland area (80,000 ha), and a salt-aﬀected area (1, 80,000 ha), producing 58,000 metric tons of fish against the estimated production potential of 90,000 metric tons. The cumulative annual growth rate of fish production of 9.35 % has been recorded during the last 19 years. About 50,000 fishers, farmers, and entrepreneurs are engaged directly and indirectly in fisheries-related activities. The linear regression forecasting model shows the beta/coefficient value was 271.72 of fish seed production; that is, if fish seed production increases by 1%, the fish production will increase by about 271 tons, and the fish production will increase to 85.91 MT by 2030. A literature review shows that the resources are underutilized and have a huge potential for fish production and livelihood development if the issue like unavailability of quality seed, lack of technical inputs, inadequate awareness programs, insufficient research eﬀorts, and a deficiency of professionals from the fisheries sector, is addressed. However, opportunities in the fisheries sector may be fashioned by adopting innovative approaches such as cage culture, ornamental fisheries, freshwater pearl, inland saline aquaculture.